Detection of melatonin and 5-HTP in dietary supplements based on multiple spectra - Yang, Huiyu; Zhang, Xinrui; Gao, Yang; Peng, Zhuang; Su, Bo; Li, Kai; Zhang, Cunlin (Frontiers in Nutrition, 2025)
IntroductionMelatonin and 5-hydroxytryptophan (5-HTP), known for benefits in regulating sleep and combating depression, respectively, are incorporated into dietary supplements. Rapid and accurate identification of dietary supplement types and their contents remains a significant challenge in ensuring food safety.MethodsIn this study, qualitative and quantitative analysis of melatonin and 5-HTP was performed using Raman spectroscopy, powder X-ray diffraction (PXRD), and terahertz time-domain spectroscopy (THz-TDS). Purity and crystal structures of the samples were investigated using Raman spectroscopy and PXRD, establishing the foundation for terahertz (THz) simulations.Results and discussionThe Raman spectroscopy results demonstrate that the characteristic Raman peaks of melatonin and 5-HTP in the range from 170 cm−1 to 1700 cm−1 were observed at 1356 cm−1 and 1,304 cm−1, respectively. Results of THz revealed that melatonin and 5-HTP each have five THz characteristic peaks, which distinguish these substances. The peak of melatonin at 1.23 THz shows a good linear fit with the mass fraction, while 5-HTP has a similar relationship at 1.14 THz. Then, L-tryptophan, a common contaminant in the production of melatonin and 5-HTP, was successfully identified within the mixture. Finally, it is demonstrated that THz technology can effectively detect melatonin and 5-HTP in commercial dietary supplements. This study establishes a rapid, efficient, and non-destructive approach for the regulation and quantitative analysis of dietary supplements.